A National Swedish Longitudinal Twin‐Sibling Study of alcohol use disorders among males. (2nd May 2017) - Long, Elizabeth C.; Lönn, Sara L.; Sundquist, Jan; Sundquist, Kristina; Kendler, Kenneth S.
Abstract: Aims: To examine whether genetic influences on the development of alcohol use disorders (AUD) among men during emerging adulthood through mid‐adulthood are stable or dynamic. Design: A twin study modeling developmental changes in the genetic and environmental influences on AUD during three age periods (18–25, 26–33 and 33–41) as a Cholesky decomposition. Setting: Sweden. Participants: Swedish male twin pairs (1532 monozygotic and 1940 dizygotic) and 66 033 full male sibling pairs born less than 2 years apart. Measurements: AUD was identified based on Swedish medical and legal registries. Findings: The best‐fitting model included additive genetic and unique environmental factors, with no evidence for shared environmental factors. Although the total heritability was stable over time, there were two major genetic factors contributing to AUD risk, one beginning at ages 18–25 with a modest decline in importance over time [0.84; confidence interval (CI) = 0.83–0.88], and another of less impact beginning at ages 26–33 with a modest increase in importance by ages 33–41 (0.31; CI = 0.05–0.47). Conclusions: The heritability of alcohol use disorders among Swedish men appears to be stable among three age periods: 18–25 years, 26–33 years, and 33–41 years. Two sets of genetic risk factors contribute to alcohol use disorders risk, with one originating during the ages 18–25 years and another coming online at 26–33 years, providing support for the developmentally dynamic hypothesis.